Study of Dynamic Properties of R/C Building using Numerical FEM Modeling Simulation and Experimental Ambient noise Measurements (Damascus University Journal for engineering sciences, 2022)
Experimental studies are the basis for knowing the actual response of structures under seismic forces during earthquakes, this is very important to design an earthquake resistant structures. But, the high cost of such experiments on actual structures or scaled models makes it unfeasible. Therefore, numerical modeling of structures that simulate the actual ones using numerical simulation methods such as finite element method became very important. However obtaining a numerical model of a structure needs to be validated against incorrrect analysis results. In this research a validation study to compare the numerical simulation results with experimental results are needed. These experiments should be cost-effective to obtaining the desired results. Ambient noise measurements. And thereby comparing the experimental results with the numerical simulation results validated the accuracy of the numerical model as it demonstrated the model to be accurate. The ambient noise measurements which were performed in this research; and the numerical model which was developed gave satisfactorily close results when they were compared.
Keywords: Dynamic Properties, Eigenvalue problem; Frequency analysis; Finite element modeling; Time-history nonlinear analysis; Modal testing; Ambient Vibration measurements; Spectral Ratios